Sclerosing treatment of varicose veins - Mazza Bruno, Milton; Del Campo, Alberto; Mate, Miguel; Gomez Fossati, Carlos; Sanguinetti, Julio; Bayardo, Gladys (Cirugía del Uruguay, 1971)
The paper studies the sclerosing treatment of varicose veins. Stress is laid on the need of admitting that treatment of varicose veins should combine surgery and sclerosis. Surgery still comes first, but the sclerosing treatment has its special app!ication. The mechanism whereby sclerosing substances act, as well as the characteristics of the latter, are analyzed; and the technique of sclerosing injections and possible complications, arising thereof, are discussed.